EFEKTIFITAS KOMBINASI METODE DEMONSTRASI DAN LATIHAN UNTUK MENINGKATKAN KEMAMPUAN MENCUCI BAJU - Elnang Finaros (Universitas Negeri Padang, 2012)
This research aim to to increase ability clean clothes embisil of child by using combination demonstrate and practice method. This research use approach of Single Subject Reaserch ( SSR) with A-B desain. Subject Research is embisil of child (X). It’s goals measure of him that is how many amount (%) stages; steps clean clothes which have been specified can clean better and correctness. Where condition A (baseline) that is condition of early before given condition and treatment B that is represent the condition of intervention namely the condition of where child given intervention by using combination demonstrate and practice method. Result of this research indicate that ability of child in cleaning clothes mount after given study with method demonstrate and practice. This proven phase of baseline (A) ability of child still lower (12,5%). After given by intervention ( B) through treatment with combination demonstrate and practice method, ability of child mount until (87,5%) in do step to clean clothes which have been specified better and correctness. From result of presentation of data can be concluded that combination demonstrate and effective practice method to increase ability clean clothes embisil of child. This research expected can be of benefit to researcher and teacher hereinafter and in order to become guidance to do combination demonstrate and practice method to increase ability embisil of child in managing the other ownself.